A Randomized, Double-Blinded, Placebo-Controlled Clinical Trial Evaluating the Effectiveness of Daily Vibration After Arthroscopic Rotator Cuff Repair. (November 2015) - Lam, Patrick H.; Hansen, Kaitlyn; Keighley, Geffrey; Hackett, Lisa; Murrell, George A.C.
Background: Rotator cuff repair is a common method to treat rotator cuff tears; however, retear rates remain high. High-frequency, low-magnitude vibration has been demonstrated to promote new bone formation in both animal models and in humans. Hypothesis: This type of mechanical stimulation applied postoperatively will enhance tendon-to-bone healing and reduce postoperative retear rates. Study Design: Randomized controlled trial; Level of evidence, 1. Methods: A randomized, double-blinded, placebo-controlled clinical trial was conducted to investigate the effects of 5 minutes of 80-Hz vibration applied daily after arthroscopic rotator cuff repair for 6 months on postoperative rotator cuff healing. The primary outcome was ultrasound-assessed repair integrity at 6 months after repair. Recruited patients were randomized into 2 groups: one group received a vibration device that oscillated at 80 Hz, and the other group received a placebo device. Results: The postoperative retear rates of both groups were similar (9.1% [5/55] in the vibration group, and 9.3% [5/54] in the placebo group) at 6 months as determined by ultrasound imaging. Vibration did provide acute pain relief at 6 weeks after surgery (visual analog scale [VAS] score, 2.24 ± 0.29 cm) compared with placebo (VAS score, 3.67 ± 0.48 cm) ( P < .003). Six months after surgery, both groups had significant reductions in pain during overhead activities, at rest, and during sleep and overall shoulder pain compared with before surgery ( P < .001). Both the vibration and placebo groups had significant increases in shoulder strength with abduction in the scapular plane, adduction, liftoff, internal rotation, and external rotation 6 months after surgery. Statistical analysis showed that vibration was not a contributing factor at improving these parameters in these periods. Conclusion: High-frequency, low-magnitude vibration did provide acute pain relief on application 6 weeks after arthroscopic rotator cuff repair surgery. However, vibration did not improve tendon-to-bone healing, shoulder range of motion, shoulder strength, or shoulder pain with activities, at rest, and at night when compared with placebo.